2020
DOI: 10.21203/rs.3.rs-51400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential long-term consequences of school closures: Lessons from the 2013-2016 Ebola pandemic

Abstract: The COVID-19 pandemic has seen an unprecedented shutdown of society. Nearly 1.725 billion children across the globe have been affected as over 95% of countries closed schools as the virus spread in April 2020. Much attention has been given to school closures as non-pharmaceutical mitigation tools to stem the spread of the disease through ensuring social distancing. Within education, focus has been given to keep students connected through remote learning and the immediate needs of schools upon reopening. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…33 34 These impacts disproportionately affect lower income and more marginalised students and particularly older adolescents who take on additional paid or unpaid work during crises. 35 36 Studies have shown that once engaged in economic activities, older adolescents may have to retain these responsibilities even after schools reopen to help sustain their families. 30 35 36 Our results echo these findings, showing how girls engaged in non-school-related work had increased work hours in the aftermath of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 34 These impacts disproportionately affect lower income and more marginalised students and particularly older adolescents who take on additional paid or unpaid work during crises. 35 36 Studies have shown that once engaged in economic activities, older adolescents may have to retain these responsibilities even after schools reopen to help sustain their families. 30 35 36 Our results echo these findings, showing how girls engaged in non-school-related work had increased work hours in the aftermath of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…During Ebola many countries employed school closures as a policy response to contain the outbreak; however, long after schools reopened, school enrolment of young girls remained significantly lower than pre-Ebola 33 34. These impacts disproportionately affect lower income and more marginalised students and particularly older adolescents who take on additional paid or unpaid work during crises 35 36. Studies have shown that once engaged in economic activities, older adolescents may have to retain these responsibilities even after schools reopen to help sustain their families 30 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between child labour and pandemics has been selected due to its importance. The study concludes that as for the relation between previous pandemics and child labour, it was observed that there was increased interest in the African countries (e.g., Nyambedha et al 2003;Lugalla and Sigalla 2010;Evans 2012;Sorsa and Abera 2016), including the post-war economies (e.g., Save the Children/UNICEF/World Vision/Plan International 2015; Ngegba and Mansaray 2016;Yoder-van den Brink 2019;Smith 2020). On the contrary, the researchers who investigated the impact of COVID-19 on child labour mostly focused on the case of the Asian economies (e.g., Chopra 2020;Larmar et al 2020;Ramaswamy and Seshadri 2020;Kaur and Byard 2021;Daly et al 2021).…”
Section: Discussion and Suggestionsmentioning
confidence: 88%
“…In addition, certain studies predicted psychosocial and mental health problems and concluded that pandemics affect children's wellbeing (e.g., Ngegba and Mansaray 2016; Yoder-van den Brink 2019; Ramaswamy and Seshadri 2020), while others observed that pandemics could reduce school attendance and increase dropout rates (e.g., Gicharu et al 2015;Smith 2020) and Yoder-van den Brink (2019) argued that school closures could increase child labour, focusing on Sierra Leone. Finally, insufficient protection services were observed in several developing countries and this was related to child labour (e.g., Chopra 2020; Kaur and Byard 2021).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Research has been conducted on the previous health crises (such as the Spanish flu, H1N1, and the Ebola epidemics) and their impact on children's education in other countries. It has been shown that such a crisis had not only cost lives and employment but had also substantially deteriorated learning achievement and dropout of school-age children (Amorim et al, 2020;Elston et al, 2017;Fischer et al, 2018;Percoco, 2016;Smith, 2020).…”
Section: Review Of Existing Literaturementioning
confidence: 99%